PERAN MOTIVASI ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA SD NEGERI 2 TOLITOLI - Nasriani, Nasriani (Journal of Innovation Research and Knowledge, 2024)
The Role of Presents’ Motivation of improving student achievement at SD Negeri 2 Tolitoli. The objectiver to be achieved in the implementation of this research are (1) To determine the extent of the lack of parental motivation as a factor in the decline in student achievement at SD Negeri 2 Tolitoli (2) To find out how the teacher’s technique in providing students’ motivation to learn at SD Negeri 2 Tolitoli. This research is a type of qualitative descrptive research. The date obtained are prosessed using percentages to be used in drawing conclusions. The results of the study indicate that the role of parents is very influential on increasing the learning motivation of students at SD Negeri 2 Tolitoli. And this research shows that the lock of motivation of parents in SD Negeri 2 Tolitoli causes students to be less motivated to learn. However, thanks to be effort made by the teachess at the school, it can foeter student learning motivation ar SD Negeri 2 Tolitoli